Highly efficient degradation of cypermethrin by a co-culture of Rhodococcus sp. JQ-L and Comamonas sp. A-3 - He, Jian; Zhang, Kaiyun; Wang, Lin; Du, Yingchun; Yang, Ying; Yuan, Cansheng (Frontiers in Microbiology, 2022)
Cypermethrin is an important synthetic pyrethroid pesticide that widely used to control pests in agriculture. However, extensive use has caused its residue and the metabolite 3-phenoxybenzoic acid (3-PBA) to seriously pollute the environments and agricultural products. In this study, a highly efficient cypermethrin-degrading bacterial consortium was acclimated from long-term pyrethroid-contaminated soil. Two strains, designated JQ-L and A-3, were screened from the consortium, and identified as Rhodococcus sp. and Comamonas sp., respectively. Strain JQ-L transformed 100 mg/L of cypermethrin to 3-PBA within 60 hr of incubation; however, 3-PBA could not be further degraded by the strain. Strain A-3 utilized 3-PBA as sole carbon for growth, and completely degraded 100 mg/L of 3-PBA within 15 hr of incubation. Co-culture of JQ-L and A-3 completely degraded 100 mg/L of cypermethrin within 24 hr of incubation. Furthermore, a complete catabolic pathway of cypermethrin and the metabolite 3-PBA by the co-culture was proposed. This study provided a promising strategy for efficient elimination of cypermethrin residue-contaminated environments and agricultural products.